Characterization of the main character in the dictator movie - Hanggur, Yulianus; A, I Wayan Resen M; Aryaningsih, Ni Nyoman Deni (Institut Pariwisata dan Bisnis Internasional, 2022)
The aim of this study is to find the types of characterization of the main character found in The Dictator movie. This study used the theory proposed by (Kennedy 1996; 28) in analyzing the types of characterization of main character Wellek and Warren (1956) which was used in analyzing the characterization of the main character. The data were qualitatively analyzed and presented descriptively based on theories adopted in this research. The result of this research shows that there are two types of the character namely antagonist and protagonist character. In showing the types of character and characterization of the main character the writer used some dialogue from the movie. There are three aspects of the characterization of the main character found in The Dictator movie. There are physiological dimensions, physiological dimensions, and sociological dimensions.